Effect of Melatonin and Analogues on Corneal Wound Healing: Involvement of Mt2 Melatonin Receptor. (January 2015) - Crooke, Almudena; Guzman-Aranguez, Ana; Mediero, Aranzazu; Alarma-Estrany, Pilar; Carracedo, Gonzalo; Pelaez, Teresa; Peral, Assumpta; Pintor, Jesús
Abstract Purpose: We have investigated the effect of melatonin and its analogues on rabbit corneal epithelial wound healing. Methods: New Zealand rabbits were anaesthetised and wounds were made by placing Whatman paper discs soaked in n-heptanol on the cornea. Melatonin and analogues (all 10 nmol) were instilled. Wound diameter was measured every 2 hours by means of fluorescein application with a Topcon SL-8Z slit lamp. Melatonin antagonists (all 10 nmol) were applied 2 hours before the application of the n-heptanol-soaked disc and then every 6 hours together with melatonin. To confirm the presence of MT2 receptors in corneal epithelial cells immunohistochemistry, Western blot and RT-PCR assays in native tissue and in rabbit corneal epithelial cells were performed. The tear components were extracted then processed by HPLC to quantify melatonin in tears. Results: Migration assays revealed that melatonin and particularly the treatment with the MT2 agonist IIK7, accelerated the rate of healing (p < 0.001). The application of the non-selective melatonin receptor antagonist luzindole and the MT2 antagonist DH97 (but not prazosin), prevented the effect of melatonin on wound healing (both p < 0.001). Immunohistochemistry, Western blot and RT-PCR assays showed the presence of MT2 melatonin receptor in corneal epithelial cells. In addition, we have identified melatonin in tears and determined its daily variations. Conclusions: These data suggest that MT2 receptors are implicated in the effect of melatonin on corneal wound healing regulating migration rate. This suggests the potential use of melatonin and its analogues to enhance epithelial wound healing in ocular surface disease.